Quality improvement of undergraduate courses based on fuzzy analytic hierarchy process and entropy method - Peng, Aotian (Frontiers in Psychology, 2022)
Since curriculum is the core carrier to improve the level of talent cultivation in colleges and universities, strengthening the reform of course teaching and improving the quality of course teaching are the fundamental to the survival and development of colleges and universities, and also an important part of higher education reform. In this paper, fuzzy analytic hierarchy process (AHP) and entropy method were used to determine the weight of the core evaluation indicators of undergraduate course quality improvement, including four first-level indicators of curriculum concept, curriculum resources, curriculum organization and curriculum effectiveness, and 12 second-level evaluation indicators and weights. Then, based on a case study of the first-class undergraduate course “Management” of Anyang Normal University, the way to evaluate the course by AHP and entropy method were explained. Finally, according to the evaluation results, the ideas of course construction were put forward, such as changing the course concept, enriching the course resources, paying attention to the course organization and ensuring the course effectiveness, so as to improve the quality of undergraduate courses, and then improve the quality of undergraduate talents training with the improvement of course quality as the starting point.